Telenursing Asuhan Keperawatan pada Lansia dengan Covid 19: Case Report - Ummi Malikal Balqis; Asep Suryadin (Journal of Health Science and Prevention, 2022)
The COVID-19 pandemic has had an impact on health systems in many countries, including Indonesia. From this crisis, nurses as one of the front lines in COVID-19 health services have an important role in providing nursing services for self-isolated patients at home through family care's telenursing services. Teh Method of this study uses a case report design in 1 case of a family with an elderly confirmed positive for covid 19 that carried out through virtual monitoring with a telenursing approach. Observation and analysis of the case report of family care's telenursing based on the 5 Family Health Task (FHT) approach according to Maglaya's theory associated with NANDA-NOC-NIC International. The Results study shows that the family care's telenursing helps the elderly and families recognize the covid 19 problems, making decisions for appropriate treatment, caring for the elderly through telenursing, modifying a healthy environment for the elderly, and utilizing telenursing so that this program can effectively help families and the elderly achieve maximum health status during the self-quarantine period in Home. This study is expected to be a reference for related institutions to develop family care's telenursing in providing family nursing care for families with COVID-19 problems